The freedom of scientific research in international law: outer space, the Antarctic and the oceans - Institut universitaire de hautes études internationales (Switzerland). degree granting institution; Graham, Gerald (Université de Genève, 1981)
Ph. D. thesis no. 332, Université de Genève Includes bibliography